Preoperative thyroid stimulating hormone level as risk factor for differentiated thyroid cancer - Moustafa, Asem Fayed; Ammar, Mohammed Sabery; El-Hantour, Asmaa; El-Kased, Ahmed Farag (International Surgery Journal, 2019)
Background: The objective of the study was to explore the relationship between TSH and differentiated thyroid cancer. Methods: From September 2017-September 2018, two groups included 247 euthyroid patients with thyroid swelling who had thyroidectomy studied retrospectively and prospectively by observing preoperative TSH level. Euthyroid adult patients with differentiated thyroid cancer and benign thyroid conditions and euthyroid patients with any thyroid diseases who will going to have thyroidectomy were included otherwise other thyroid conditions were excluded. Patients were classified into 192 retrospective cases (Group I) and 55 prospective cases (Group II). Results: Increased age of malignant cases with a female predominance. All cases presented with a neck swelling. Clinically in group I nodular swelling in 156 cases (81.2%), diffuse swelling in 36 cases (18.8%) and in group II, nodular swelling in 47 cases (85.5%) and diffuse swelling in 8 cases (14.5%). Histopathology of group I thyroid adenoma in 5 cases (4.8%) and multinodular goiter in 100 cases (95.2%). In addition 80 cases (92%) were papillary carcinoma and follicular carcinoma in 7 cases (8%) while in group II; multinodular goiter in29 cases (100%) and papillary carcinoma in 21 cases (80.8%) as well as follicular carcinoma in 5 cases (19.2%) in malignant cases. Group I showed a significant increase in TSH in malignant cases with the same finding in group II. Conclusions: TSH is an indicator for thyroid malignancy and FNAC biopsy is recommended for thyroid swellings showed elevated TSH.